Challenging live performance: Dance on Social Media for Wellbeing and to Resist Dance Quarantine during the 2020 Covid-19 - Chamba Nana, Mirelle Flore (UIR Press, 2023)
This paper argues that the uptake of social media by the dance community due to COVID-19 challenges the conventional consideration of dance as a live performance and gratifies people with wellbeing experiences. Grounded on Digital Research Method and Theoretical sampling, findings reveal that though the dance community was seriously impacted by the COVID-19 in 2020, they challenged space by re-defining innovative strategies that fuse with the digital world to limit stress, recreate a social connection and empathy. As a strong response to COVID-19, dancers invaded the social media, stimulating various ways to observe, create, and understand space during confinement.